2019
DOI: 10.1177/0885328219845969
|View full text |Cite
|
Sign up to set email alerts
|

Nano-amorphous calcium phosphate doped with citrate: Fabrication, structure, and evaluation of the biological performance

Abstract: Amorphous calcium phosphate, a precursor phase of the bone mineral in vertebrates, is limited owing to its instability. A simple wet-chemical precipitation method was developed in this study to prepare stable and nanosized amorphous calcium phosphates doped with citrate using orthophosphoric acid, anhydrous critic acid, and anhydrous calcium chloride as the raw materials in an alcohol system at room temperature. The structure of the obtained nanosized amorphous calcium phosphate doped with citrate was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Moreover, it is found that the n-ACP owns the higher reactivity, biological activity, and biocompatibility due to its larger specific surface area, but n-ACP is unstable. As our previous work [4], the results suggested that we successfully obtained the stable n-ACP doped with citrate (n-ACP-cit). Hence, the stable n-ACP-cit could be considered as a promising filling material owing to their biocompatible and bioactive properties in bone repair and regeneration.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Moreover, it is found that the n-ACP owns the higher reactivity, biological activity, and biocompatibility due to its larger specific surface area, but n-ACP is unstable. As our previous work [4], the results suggested that we successfully obtained the stable n-ACP doped with citrate (n-ACP-cit). Hence, the stable n-ACP-cit could be considered as a promising filling material owing to their biocompatible and bioactive properties in bone repair and regeneration.…”
Section: Introductionsupporting
confidence: 68%
“…The n-ACP-cit/PAA composites were synthesized using melt extrusion method. Firstly, n-ACP-cit powder was prepared according to our previous publication [4]. Secondly, PAA copolymer was obtained as followings: 6.56 g Lhydroxyproline, 8.91 g L-alanine, 36.09 g γ-aminobutyric acid, and 65.59 g 6-aminocaproic acid (Shanghai Experimental Reagents Co., Ltd., China) were added to a 250.00 ml reaction flask.…”
Section: Preparation Of N-acp-cit/paa Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the scientific literature, the synthesis of ACP is usually described as a simple one-step process; on the contrary, ACPC is synthesized by a multistep process. As shown in Figure , Scheme 1, the precursor of COO – -containing small organic molecules is either used in the acidic or basic form, which can lead to variation in pH, making the reaction tedious, expensive, and affecting the final product. Moreover, ACP/ACPC reactions are rapidly performed at alkaline pH.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis mechanism of ACPC. Scheme 1 represents the traditional synthesis approach in which citrate is used as an acid or a base. The reaction of ACPC synthesis is rapid, and due to the triprotic nature of phosphate, fluctuation in pH disturbs the protonated forms of phosphates, which can affect the final product. Scheme 2 represents our synthesis approach in which citrate was used as a calcium salt, and pH adjustments were made before mixing of calcium and phosphate sources.…”
Section: Introductionmentioning
confidence: 99%